Work-related musculoskeletal disorders in nursing: current knowledge and ongoing challenges for occupational health - Serranheira, Florentino; Smith, Derek (La Medicina del Lavoro, 2014)
Work-related Musculoskeletal Disorders (MSD) represent a major occupational health concern when considering the relationships between work and disease but associations between MSD and hospital work, especially in the nursing profession, aren't yet full understanded.QMSDuestions that still need to be answered include: Are nurses’ work-related musculoskeletal symptoms and injuries dependent on the wards, the hospital organization and even the national occupational health policies that they originated from? Is their MSD related with workplaces demands, equipment, and nurse-patient ratios? Do these factors highlight different nursing occupational exposure to MSD hazards? What are the individual and psychosocial contributes to nurses WRMSDs in different nursing contexts? As such, a new approach which integrates more realistic working conditions, real hospital equipment, workplace features, and individual information would likely be a better way forwards in the addressing the current MSD epidemic among hospital nurses, worldwide......